2017
DOI: 10.1038/s41598-017-13029-4
|View full text |Cite
|
Sign up to set email alerts
|

Renal iron accumulation occurs in lupus nephritis and iron chelation delays the onset of albuminuria

Abstract: Proteins involved in iron homeostasis have been identified as biomarkers for lupus nephritis, a serious complication of systemic lupus erythematosus (SLE). We tested the hypothesis that renal iron accumulation occurs and contributes to renal injury in SLE. Renal non-heme iron levels were increased in the (New Zealand Black x New Zealand White) F1 (NZB/W) mouse model of lupus nephritis compared with healthy New Zealand White (NZW) mice in an age- and strain-dependent manner. Biodistribution studies revealed inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 54 publications
(59 reference statements)
4
31
1
Order By: Relevance
“…Iron accumulation has been observed in nephritic kidneys. 22 As hepcidin affects systemic iron stores, we evaluated renal and splenic iron accumulation and its relation to the outcome of LN. Compared with PBS-treated mice, the kidneys of hepcidin-treated mice contained less Perl's stainable iron in tubules and interstitial regions (Supplementary Figure S1A).…”
Section: Hepcidin Treatment Reduces the Severity Of Ln And Renal Ironmentioning
confidence: 99%
See 1 more Smart Citation
“…Iron accumulation has been observed in nephritic kidneys. 22 As hepcidin affects systemic iron stores, we evaluated renal and splenic iron accumulation and its relation to the outcome of LN. Compared with PBS-treated mice, the kidneys of hepcidin-treated mice contained less Perl's stainable iron in tubules and interstitial regions (Supplementary Figure S1A).…”
Section: Hepcidin Treatment Reduces the Severity Of Ln And Renal Ironmentioning
confidence: 99%
“…mice 22 and deferiprone, a U.S. Food and Drug Administration-approved iron chelator, delayed the onset of albuminuria, thereby highlighting iron metabolism as a potential therapeutic target.…”
mentioning
confidence: 99%
“…53 Also Marks et al, reported that the mentioned iron chelator could delay the onset of albuminuria and reduced BUN concentrations. 15 It should be noted that due to the role of iron in different vital processes, especially hematopoiesis, any interventions by chelation therapy must have no negative effects on iron-related physiological parameters, and due to the importance of this, in the present study, hepatic iron content and RBC count, Hb, Hct and MCV levels were assayed, the results of which showed no negative effects of using BCc1 on important iron-related physiological parameters. On the other hand, this nanomedicine significantly decreased urine MDA and 8-isoprostane concentration as the well-known markers of oxidative stress, 54,55 and previous studies have already proved that the production of these markers is closely related to iron metabolism disruption.…”
Section: Discussionmentioning
confidence: 66%
“…46 To break the harmful cycle, several studies have evaluated the effects of iron chelators in these situations. [14][15][16][17] In the previous studies, anti-neoplastic effects of BCc1 nanomedicine with iron-chelating property were demonstrated in several experiments. 19,20,47 In the present study, this nanomedicine was tested in animal model of DKD to evaluate its impacts on various biochemical and histopathological parameters of this disease.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation